DINAMIKA RAKIT DI ATAS KONVEKSI RAYLEIGH-BENARD RAFT DYNAMICS ON THE RAYLEIGH-BENARD CONVECTION - , DEWI LITA MARTANTI, Dr. Eng. Fahrudin Nugroho, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Convection is a phenomenon widely observed in nature. To study the phenomenon of convection in a laboratory scale is commonly used fluid observation device. This device uses a fluid system, which is heated from below, that is called Rayleigh-Benard Convection (RBC). Silicone oil as the fluid mixed with grinding paste was put in a cylindrical chamber with an aspect ratio L = 10=1. Temperature difference between the bottom plate and the top plate is represented by the control parameter , which is = (T ô Tc)=Tc. The observation results show that the system is in a steady state at < 0, and it starts unstable at > 0 that phenomena of convection begin to occur. Increasing the value of is followed by transitions of thermal convection patterns on the fluid surface. Homogeneous raft which is floated on the fluid surface is then observed and it is found the dynamics raft motion that are linear and oscillatory motions.